Plasma Exosomes as Markers of Therapeutic Response in Patients with Acute Myeloid Leukemia - Hong, Chang-Sook; Muller, Laurent; Whiteside, Theresa L.; Boyiadzis, Michael (Frontiers in Immunology, 2014)
Purpose: Exosomes isolated from the plasma of newly-diagnosed acute myeloid leukemia (AML) patients have elevated protein and TGF-β1 contents and inhibit natural killer (NK) cell cytotoxicity. A potential role of exosomes in predicting responses to chemotherapy (CT) was evaluated in AML patients undergoing treatment. Experimental Design: Plasma was obtained from AML patients at diagnosis (n=16); post induction CT (n=9); during consolidation CT (n=10); in long-term remission (LTCR, n=5); and from healthy volunteers (n=7). Exosomes were isolated by exclusion chromatography and ultracentrifugation. The exosomal protein, soluble TGFβ-1 levels (ELISA) and the TGF-β1 profiles (western blots) were compared among patients’ cohorts. The results were correlated with the patients’ cytogenetic profile, percentage of leukemic blast and outcome. Results: At diagnosis, protein and TGF-β1 levels were higher (p< 0.009 and p< 0.004) in AML than control exosomes. These values decreased after induction CT (p< 0.05 and p< 0.004), increased during consolidation CT (p< 0.02 and p< 0.005) and normalized in LtCR. While TGF-β1 and protein levels tracked one another, TGF-β1 propeptide, latency-associated peptide (LAP) or mature TGF-β1 differentially decorated exosomes isolated before, during and after CT. Only TGF-β1 propeptide was seen in exosomes of controls or LtCR patients. During consolidation CT, exosomes carried TGF-β1 propeptide, LAP and low levels of mature TGF-β. NK cell co-incubation with AML exosomes carrying all three TGF-β1 forms induced down-regulation of NKG2D expression. Conclusions: Changes in exosomal protein and/or TGF-β1 content may reflect responses to CT. The exosomal TGF-β1 profile suggests the presence of residual disease in patients considered to have achieved complete remission.